Parenting Practices Dalam Perkembangan Psikoseksual Pada Anak : (Studi Kasus Pada Anak Yang Memiliki Perilaku Seksual) - Ainayya Nahdahunnisa; M. Daud; Rohmah Rifani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Psychosexual development in children is influenced by the parenting practices parents use at each stage of psychosexual development. When parenting practices are used inappropriately, it will create obstacles to their psychosexual development. This study aims to find out how parenting practices are used in psychosexual development in children. The research method used is qualitative with a case study approach. Data collection techniques used are interviews and observation. Verification of the research data used is the triangulation technique. This research involved two respondents aged seven and nine years and two significant others, namely the respondent's mother and cousin. The results of the research are that there are obstacles in the respondent's psychosexual development, the parenting patterns used by the respondent's mother are parenting practices, punitive discipline, incoherence, warmth and positive involvement, and spanking. The sexual behavior carried out is imitated by the mother and family members as well as the impact of social media. The implication of this research is as input for parents to be able to avoid parenting patterns that hinder the process of psychosexual development which causes children to have sexual behavior.